DISIPLIN PASAR DAN MORAL HAZARD BANK - Nur Ariani Aqidah (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2017)
This paper aims to explain the relationship between market discipline and moral hazard banks. Market discipline is one of the three pillars formed by the Basel Committee in improving banking performance and transparency through supervision carried out by depositors. While moral hazard is high risk taking by the bank. Market discipline and bank moral hazard can be understood using agency theory.